1999
DOI: 10.1007/s002470050641
|View full text |Cite
|
Sign up to set email alerts
|

Lipoblastoma: MRI appearances of a rare paediatric soft tissue tumour

Abstract: Lipoblastoma is a rare, benign soft-tissue tumour derived from embryonic fat. Four patients with tumours located in the upper limb are reported, with special reference to imaging techniques and histology. Radical surgical excision is essential to prevent local recurrence and exact imaging techniques are thus crucial. MRI appears to be a reliable preoperative investigation and is the recommended radiological examination. In a child under 3 months of age, images showing a predominantly fatty but inhomogeneous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 3 publications
0
24
0
3
Order By: Relevance
“…Lipoblastoma must be suspected in a child < 3 years of age with a predominantly fatty, nonhomogeneous, soft tissue mass on MRI. 29 In the literature, cytologic findings of six FNA cases of lipoblastoma [13][14][15][16][17] and one intraoperative smear are reported. 31 In these reports, the cytologic specimens consist of viscous, mucoid fluid with small, white tissue fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoblastoma must be suspected in a child < 3 years of age with a predominantly fatty, nonhomogeneous, soft tissue mass on MRI. 29 In the literature, cytologic findings of six FNA cases of lipoblastoma [13][14][15][16][17] and one intraoperative smear are reported. 31 In these reports, the cytologic specimens consist of viscous, mucoid fluid with small, white tissue fragments.…”
Section: Discussionmentioning
confidence: 99%
“…In the present report, the patient age was relatively old and it was difficult to make a differential diagnosis between myxoid liposarcoma and lipoblastoma. Reiseter et al (1999) reported that MRI is an essential tool for diagnosis and preoperative evaluation of lipoblastoma. MRI can show anatomical detail, which is essential for successful radical tumor excision.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoblastoma is a rare benign soft-tissue childhood tumor occurring most commonly in children less than 3 years of age (Chung and Enzinger 1973;Mentzel et al 1993), and magnetic resonance image (MRI) is a useful tool for its diagnosis and preoperative evaluation (Reiseter et al 1999). MRIs of this type of tumor are typically characterized by high-intensity signals on both T1 weighted (T1-W) and T2 weighted (T2-W) images (Letourneau et al 1993).…”
mentioning
confidence: 99%
“…-A fatty component is suggestive of a benign lesion such as lipoblastoma (Fig. 9) [15], fibrolipomatous hamartoma, lipoma or dermoid cyst since liposarcomas are exceptional and generally not observed before the age of 10 years [3]. Therefore, in childhood, when fatty lesions are observed, a morphologic characterization by magnetic resonance may be a sufficient basis on which to make critical therapeutic judgments [32].…”
Section: How To Analyze the Images?mentioning
confidence: 99%
“…5). More rarely, demonstration of bone hypertrophy may indicate an arteriovenous malformation or diffuse lipomatosis [15]. Analysis of soft tissues must look for calcifications and fat density areas.…”
Section: Conventional Radiographymentioning
confidence: 99%